Professional aspirations as indicators of responsible leadership style and corporate social responsibility : Are we training the responsible managers that business and society need? A cross-national study - Sánchez, Flor; Sandoval, Angelica; Rodríguez Pomeda, Jesús; Casani, Fernando (Madrid : Colegio Oficial de Psicólogos de Madrid, 2020)
The relationship between responsible leadership (RL), identified from achievement expectations, and the importance attached to corporate social responsibility (CSR) was analyzed. In a survey of 1,833 business management undergraduates in six Ibero-American countries, factor analysis identified three approaches to stakeholder relations, behaviors, and professional aspirations: a relational style associated with the intention to collaborate with others; a pragmatic style geared to attaining personal and organizational objectives; and an individualist style informed by a drive for personal achievement. Regression analyses confirmed the relationship between relational and pragmatic styles and CSR geared to stakeholder well-being, protection of social and natural environments, and ethical management. Both were associated with regard to the responsibilities that ensure business survival (such as meeting customer needs), while the individualist style was aligned with hostility toward those dimensions of CSR. These findings suggest that the relational and pragmatic styles lead to more effective CSR management.
En inglés; resúmenes en español e inglés.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Journal of work and organizational psychology, vol. 36, n. 1 (April 2020), P. 49-61.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Aspiraciones profesionales; Gestión empresarial; Liderazgo responsable; Mentalidad de sostenibilidad; Responsabilidad social corporativa; Artículos electrónicos.